2022
DOI: 10.3389/fendo.2022.927329
|View full text |Cite
|
Sign up to set email alerts
|

Molecular mechanisms underlying the role of hypoxia-inducible factor-1 α in metabolic reprogramming in renal fibrosis

Abstract: Renal fibrosis is the result of renal tissue damage and repair response disorders. If fibrosis is not effectively blocked, it causes loss of renal function, leading to chronic renal failure. Metabolic reprogramming, which promotes cell proliferation by regulating cellular energy metabolism, is considered a unique tumor cell marker. The transition from oxidative phosphorylation to aerobic glycolysis is a major feature of renal fibrosis. Hypoxia-inducible factor-1 α (HIF-1α), a vital transcription factor, senses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(19 citation statements)
references
References 131 publications
0
18
0
1
Order By: Relevance
“…One of the characteristics of DKD is ECM accumulation, which eventually leads to glomerular sclerosis and fibrosis ( Doi et al, 2018 ). Studies have demonstrated that HIF-1α promotes aberrant glycolysis, which finally leading to ECM accumulation and renal fibrosis in mouse models of chronic/hypoxic renal injury models ( Cai et al, 2020 ; Wei et al, 2022 ). Our diabetic db/db mice showed the pro-fibrotic activities in the kidney accompanied by kidney dysfunction and increased proteinuria and kidney injury in this study, indicating that our diabetic model presented with progressive DKD.…”
Section: Discussionmentioning
confidence: 99%
“…One of the characteristics of DKD is ECM accumulation, which eventually leads to glomerular sclerosis and fibrosis ( Doi et al, 2018 ). Studies have demonstrated that HIF-1α promotes aberrant glycolysis, which finally leading to ECM accumulation and renal fibrosis in mouse models of chronic/hypoxic renal injury models ( Cai et al, 2020 ; Wei et al, 2022 ). Our diabetic db/db mice showed the pro-fibrotic activities in the kidney accompanied by kidney dysfunction and increased proteinuria and kidney injury in this study, indicating that our diabetic model presented with progressive DKD.…”
Section: Discussionmentioning
confidence: 99%
“…Based on the difference in the α-subunits, HIFs are divided into three subtypes: HIF-1, HIF-2, and HIF-3. Reportedly, oxidative factors induced renal fibrosis by regulating the expression and activity of HIF-1 via PHD, ERK, and PI-3 K/AKT pathways [ 57 , 58 ]. Therefore, the MAPK, Ras, PI3K-Akt, FoxO, and HIF-1 signaling pathways are closely related to the occurrence and development of renal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Even in the absence of hyperglycemia, upregulation of mTOR and HIF-1 α promotes entry of glucose into cells through glucose transporter 1 (GLUT1) 1014 ; the resulting increase in glucose-6-phosphate leads to further activation of mTOR 15,16 ; and HIF-1 α promotes downstream aerobic glycolysis and lactate formation as the major sources of ATP production. 14,1719 At the same time, mTOR inhibits glucose and fatty acid oxidation by the mitochondria, 20 whose integrity is likely to be imperiled by the action of HIF-1 α and mTOR to generate reactive oxygen species. 21,22 Signaling through glucose-6-phosphate also activates the pentose phosphate pathway, thus providing ribose-5-phosphate required for nucleotide synthesis and entry into the cell cycle, 2326 a process promoted by the increase in oxidative stress.…”
Section: Nutrient Surplus and Nutrient Deprivation Signaling In Cellu...mentioning
confidence: 99%